2007
DOI: 10.1029/2007jd008888
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cycle of aerosol‐meteorology interaction over China

Abstract: [1] Weekly cycles of the concentration of anthropogenic aerosols have been observed in many regions around the world. The phase and the magnitude of these cycles, however, vary greatly depending on region and season. In the present study the authors investigated important features of the weekly cycles of aerosol concentration and the covariations in meteorological conditions in major urban regions over east China, one of the most polluted areas in the world, in summertime during the period 2001-2005/2006. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
132
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 49 publications
11
132
3
Order By: Relevance
“…Heavy precipitation usually forms in fastgrowing convective clouds, which are intimately connected with robust moisture rising caused by dynamic convergence, orographic uplifting or surface heating [2][3][4]. In contrast, low-intensity precipitation is more associated with cloud microphysical processes, which are affected by aerosols, moisture content and so on [5][6][7][8].…”
mentioning
confidence: 99%
“…Heavy precipitation usually forms in fastgrowing convective clouds, which are intimately connected with robust moisture rising caused by dynamic convergence, orographic uplifting or surface heating [2][3][4]. In contrast, low-intensity precipitation is more associated with cloud microphysical processes, which are affected by aerosols, moisture content and so on [5][6][7][8].…”
mentioning
confidence: 99%
“…Strong correlations in daily, monthly, and yearly data can persist over relatively large distances, whereas patterns in distance-decay rates for sub-daily data are normally not as clear. Aghakouchak (2010) noted that occurrence of large amounts of hourly precipitation can exhibit strong spatial dependence for sites up to 10 km apart, whereas other studies have indicated relatively weak dependencies (Serinaldi, 2008;Garcia, 2002;Barbaliscia, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…Higher air pollution may increase the amount of aerosols in the air, which influences the probability of rainfall occurrence (Bell et al 2008). This means that the accumulation of small solid particles (PM 10 ) in the air, which may increase during the weekends, could trigger the changes in the atmospheric circulations that can result in non-uniform weekly rainfall patterns (Gong et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies dealing with this phenomenon have been carried out in recent years (Bell et al 2008;DeLisi et al 2011;Gong et al 2007;Seibert et al 2013;Shultz et al 2007). In most of these studies, data on rainfall and PM 10 particles (particles with a diameter up to 10 µm) were used, and their conclusions depended on the location of the study and the selected data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation